2019
DOI: 10.5004/dwt.2019.24246
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly[3-(methacryloylamino) propyl] trimethylammonium chloride coated mesh for oil–water separation

Abstract: This study aims to prepare a polymer-coated mesh which could achieve good oil-water separation efficiency with an antibacterial property. These polymers were synthesized by the polymerization process of [3-(methacryloylamino) propyl] trimethylammonium chloride (MAPTAC). The hydrolysis resistance and the swelling ratio of the polymers were also examined in order to choose a suitable oil-water separation material. The prepared meshes showed not only high oil-water separation efficiency (>99%) with high permeate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Lin [99] studied the hydrolysis process of PDA and found that the hydrolysis velocity of the amide group on the AM unit was twice that of the quaternary ammonium salt group on the DMDAAC unit. Under alkaline conditions (10%NaOH), the intrinsic viscosity representing the velocity changed little within 90min, but decreased by 3/4 under the same conditions at 175 • C. In 2019, Wu et al [100] conducted hydrolysis resistance experiments with the synthetic homopolymers PMAPTAC and PDMC. The polymers were placed in a closed space, the reaction temperature was maintained at 50 • C, and the experiment time was 12-92 h. The results showed that at 65 h, the ester group was hydrolyzed completely, and a carboxyl group was formed.…”
Section: Hydrolytic Stabilitymentioning
confidence: 99%
“…Lin [99] studied the hydrolysis process of PDA and found that the hydrolysis velocity of the amide group on the AM unit was twice that of the quaternary ammonium salt group on the DMDAAC unit. Under alkaline conditions (10%NaOH), the intrinsic viscosity representing the velocity changed little within 90min, but decreased by 3/4 under the same conditions at 175 • C. In 2019, Wu et al [100] conducted hydrolysis resistance experiments with the synthetic homopolymers PMAPTAC and PDMC. The polymers were placed in a closed space, the reaction temperature was maintained at 50 • C, and the experiment time was 12-92 h. The results showed that at 65 h, the ester group was hydrolyzed completely, and a carboxyl group was formed.…”
Section: Hydrolytic Stabilitymentioning
confidence: 99%
“…13 MAPTAC has recently attracted considerable attention due to its high polymerization activity and antihydrolysis ability. 14,15 The polymer products with high molecular weight could be obtained due to the high polymerization activity of MAPTAC. [16][17][18] Ren B et al studied the adsorption morphology and mechanism of poly-MAPTAC and Poly-DMDAAC on kaolinite surface by density functional theory (DFT); it was concluded that the adsorption capacity of Poly-MAPTAC on kaolinite surface was higher than that of Poly-DMDAAC.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to obtain high‐molecular‐weight polymer product due to the large steric hindrance and the low polymerization activity of DMDAAC, and the enhanced flocculant's capacity of cationic polymer prepared from DMDAAC is also limited 13 . MAPTAC has recently attracted considerable attention due to its high polymerization activity and antihydrolysis ability 14,15 . The polymer products with high molecular weight could be obtained due to the high polymerization activity of MAPTAC 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies in the literature have reported on the hydrolysis of polyelectrolytes [ 9 , 10 , 11 , 12 ]. For example, in 1989, Aksberg et al [ 10 ] investigated the alkaline hydrolysis of a copolymer of acrylamide and acryloyloxyethyltrimethyl ammonium chloride P(AM-DAC) via polyelectrolyte titration and nitrogen analysis in buffered aqueous solutions at different pH ranges (3.5–8.5) and temperatures (22–50 °C).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Wu J Y et al [ 12 ] studied the hydrolysis resistance of PMAPTAC hydrogel and poly[2-(methacryloyloxy)ethyl trimethyl ammonium chloride] (PDMC) hydrogel at 50 °C under acidic conditions by potentiometric titration. The results showed that the carboxyl group concentration of PDMC hydrogel reached 64.7 mmol/g but only 0.2 mmol/g for PMAPTAC hydrogel after 65 h, implying that the hydrolysis resistance of PMAPTAC was superior to that of PDMC.…”
Section: Introductionmentioning
confidence: 99%